Empowering students in the digital era: exploring motivational factors in online education / Haslenda Yusop, Norsaliza Abu Bakar, Norlina M. Ali, Nor Fauziah Abu Bakar, Shashazrina Roslan and Nafisah Amin - Yusop, Haslenda; Abu Bakar, Norsaliza; M. Ali, Norlina; Abu Bakar, Nor Fauziah; Roslan, Shashazrina; Amin, Nafisah (UiTM Cawangan Johor, 2024)
In the era of technology, practicality, and knowledge, online learning is an educational approach that has rapidly gained attention due to the use of technology and artificial intelligence and the convenience of internet accessibility. This study aims to investigate the factors that currently motivate students to engage in online learning at public universities in Malaysia. Maintaining students' and educators' excitement and participation is equally imperative as online education continues to gain popularity. Online learning empowers students to take responsibility for self-regulation, encourage self-discipline, increase motivation, and have the ability to set and accomplish personal learning goals. Therefore, it is crucial to enable students to continuously use online learning platforms to achieve the desired outcomes. In this study, a cross-sectional was conducted by randomly selected 565 students from public higher education. The questionnaire was adapted from the survey conducted by Fowler (2018) and analysed using the Statistical Package for Social Science (SPSS). Multiple regression analysis was employed to determine the significant variables. The study found that instructor support and intrinsic goal orientation are the most critical factors influencing motivation in online learning among students. These findings are valuable insights into sustaining and enhancing motivation among students participating in online learning, contributing to the broader discussion on the practical implementation of digital educational approaches.